2019
DOI: 10.1101/510511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of long noncoding RNA GAS5 suppresses tumorigenesis and development of gastric cancer by sponging miR-106a-5p through the Akt/mToR pathway

Abstract: Long non-coding RNAs (lncRNAs) have emerged as important regulators of human cancers. LncRNA GAS5 (GAS5) is identified tumor suppressor involved in several cancers. However, the roles of GAS5 and the mechanisms responsible for its functions in gastric cancer (GC) have not been well undocumented. Herein, the decreased GAS5 and increased miRNA-106a-5p levels were observed in GC and cell lines. GAS5 expression level was significantly inversely correlated with miRNA-106a-5p level in GC tissues. Moreover, luciferas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Gastric cancer is the fourth most common malignancy, and the second most common cause of cancer-related deaths in the world [ 60 ]. GAS5 also plays a significant role as a tumor suppressor in gastric cancer [ 61 , 62 , 63 , 64 ]. A recent study highlighted the fact that GAS5 expression was significantly down-regulated in gastric cancer tissues, and that it was down-regulated in adriamycin-resistant cells [ 65 ].…”
Section: Gas5 In Tumor Therapy-related Resistanmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastric cancer is the fourth most common malignancy, and the second most common cause of cancer-related deaths in the world [ 60 ]. GAS5 also plays a significant role as a tumor suppressor in gastric cancer [ 61 , 62 , 63 , 64 ]. A recent study highlighted the fact that GAS5 expression was significantly down-regulated in gastric cancer tissues, and that it was down-regulated in adriamycin-resistant cells [ 65 ].…”
Section: Gas5 In Tumor Therapy-related Resistanmentioning
confidence: 99%
“…In gastric cancer, three miRNAs have been reported to relate to GAS5 , miR-18a [ 95 ], miR-106a-5p [ 63 ] and miR-222 [ 96 ]. In the case of miR-18a, it was reported that GAS5 directly binds to it, inhibiting tumor growth via the stimulation of the activity of natural killer (NK) cells [ 95 ].…”
Section: The Special Case Of Gas5 and Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…one study reported that the expression level of GaS5 in gastric cancer is negatively associated with that of mir-106a-5p. overexpression of mir-106a-5p reverses the biological effects induced by GaS5 overexpression, which occurs via akt/mTor (49). This shows that GaS5 overexpression serves a role in inhibiting proliferation in gastric cancer cells by inhibiting the function of mir-106a-5p, thereby reducing mTor expression (49).…”
Section: Gas5 and Mtormentioning
confidence: 79%
“…The results of the present study confirmed that mirna-106a-5p serves as an oncogene by augmenting TPTeP1-mediated stemness and radioresistance of glioma. Previous studies have demonstrated the stimulating effects of TPTeP1 and the inhibitory effect of mirna-106a-5p on cancer cell apoptosis (33,35,43). Thus, prospective studies will aim to elucidate the effect of TPTeP1 and mir-106-5p on glioma cell apoptosis.…”
Section: Discussionmentioning
confidence: 98%